Efektivitas Bahan Ajar Berbasis Local Instruction Theory dengan Pendekatan Pendidikan Matematika Realistik untuk Meningkatkan Kemampuan Penalaran Matematis - Sagita, Ni Kadek Desi Lia; Nurhanurawati, Nurhanurawati; Noer, Sri Hastuti (MATHEdunesa, 2024)
The performance of education in Indonesia was highlighted in the 2018 Program for International Student Assessment (PISA) report, particularly in mathematics, where Indonesian students ranked 72nd out of 78 countries with an average score of 379, significantly below the average set by Organisation for Economic Co-operation and Development (OECD) institutions. This underscores the urgent need to address the low mathematical reasoning abilities among Indonesian students. The aim of this research is to develop teaching materials based on Local Instruction Theory (LIT) using the Realistic Mathematics Education (RME) approach. These materials are designed to meet the criteria of validity, practicality, and effectiveness, with the goal of enhancing students' mathematical reasoning abilities. The method used in here is design research with the ADDIE model consist of five stage: analyze, design, development, implementation, and evaluation. In the first stage, we analyzed learning objectives, student characteristics, and required resources. Next, in the design stage, we developed the LIT and learning trajectories for the topic of Relations and Functions. During the development stage, we develop LIT-based teaching materials using the RME approach and conducted instrument testing to analyze the validity of the mathematical reasoning ability test instrument. At the implementation stage, the developed teaching materials were applied in the classroom. Finally, at the evaluation stage, we analyzed the research results. The research subjects were students from SMP N 2 Way Seputih, with class VIII-4 as the experimental class and class VIII-5 as the control class. The practicality of the teaching materials was rated very practical by both validators (0.77) and students (0.82). The average N-Gain score for the experimental class was higher (0.72) compared to the control class (0.67), indicating that the developed teaching materials were more effective in improving students' mathematical reasoning abilities.